1984
DOI: 10.1126/science.6436974
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-Induced Transformation of C3H 10T1/2 Cells Is Enhanced by Tumor Promoters

Abstract: The tumor promoters 12-O-tetradecanoyl-phorbol-13-acetate and teleocidin markedly enhanced the transformation of C3H 10T1/2 mouse fibroblasts when these cells were transfected with the cloned human bladder cancer c-rasH oncogene. Transfection studies with the drug resistance marker gpt and time course studies indicate that this enhancement is not simply an effect on the process of DNA transfection. These findings, together with parallel studies with NIH 3T3 fibroblasts, also indicate that the competence of ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 20 publications
4
34
0
Order By: Relevance
“…We previously reported that the potent tumor promoters 12-O-tetradecanoylphorbol-13-acetate (TPA) and teleocidin enhance the transformation of cultured rodent fibroblasts cell lines that had been transfected with the activated human oncogene c-Ha-ras T24 (11,12). Similar findings have been obtained by Dotto et al (5) for early-passage rat embryo fibroblast cultures.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We previously reported that the potent tumor promoters 12-O-tetradecanoylphorbol-13-acetate (TPA) and teleocidin enhance the transformation of cultured rodent fibroblasts cell lines that had been transfected with the activated human oncogene c-Ha-ras T24 (11,12). Similar findings have been obtained by Dotto et al (5) for early-passage rat embryo fibroblast cultures.…”
supporting
confidence: 76%
“…Similar findings have been obtained by Dotto et al (5) for early-passage rat embryo fibroblast cultures. Evidence has also been obtained that in such systems, the tumor promoters do not act simply by enhancing the process of transfection per se (5,11,12). These findings suggest that during multistage carcinogenesis, tumor promoters might act by complementing the function of activated cellular oncogenes.…”
mentioning
confidence: 72%
“…Indeed, there are several examples where the transfection of v-ras or activated c-ras into epithelial cells disturbed or blocked their terminal differentiation (10)(11)(12)(13). In fibroblastic cells, ras-activation increased their sensitivity to stimulation by growth factors (14)(15)(16)(17).…”
Section: Mechanisms Of Response Modification Involving Changes In Sigmentioning
confidence: 99%
“…Similarly, the sequencing of cDNA synthesized in vitro from the RNAs of normal tissues or tumors has revealed only a limited number of IAP subtypes (Mietz et al, 1992;Lueders et al, 1993). Finally, although it cannot be directly related to expression (but see Hojman-Montes de Oca et al, 1984;Feenstra et al, 1986;Hsiao et al, 1986 for the relationship between IAP hypomethylation and expression), Lueders et al have shown that in primary plasmacytoma only a few IAP loci are demethylated (Lueders et al, 1993;Lueders and Ku , 1995). This series of results strongly suggests that only a limited subset of IAP elements are active within a given tissue or cell line, a conclusion which is consistent with the absence of expression, in most somatic tissues, of IAPLTRs introduced in the mouse genome as transgenes (Dupressoir and Heidmann, 1996), and with the demonstration that, in the liver of old mice, 450% of the IAP transcripts actually originate from a single IAP locus (Dupressoir et al, 1995;Puech et al, 1997).…”
Section: Position E Ect For Iap Inductionmentioning
confidence: 99%
“…Actually, most studies have been concerned with tumor cell lines in culture, which may di er from the situation occurring in vivo. For instance, enhanced IAP expression and particle production (up to 1000-fold) is a common aberration of tumor cells, both from transplanted tumors and from established cell lines including myeloma and neuroblastoma (Ku and Fewell, 1985), colon tumors (Augenlicht et al, 1984), mammary tumors (Asch and Asch, 1990;Asch et al, 1993), as well as some cell lines treated with carcinogenic agents or X-ray irradiated (HojmanMontes de Oca et al, 1984;Hsiao et al, 1986;Begemann et al, 1988, see also Ronai et al, 1992). Studies on carcinogen-or viral-induced mammary carcinoma (Asch et al, 1993) and on carcinogeninduced or spontaneous hepatocellular tumors (Dragani et al, 1986(Dragani et al, , 1987 have also revealed induction of IAP expression, but only to a limited extent (i.e.…”
Section: Introductionmentioning
confidence: 99%